Prevalence and Factors Associated With Hearing Loss and Hearing Aid Use in Korean Elders - Ji-Su Kim (Tehran University of Medical Sciences, 2015)
Background: This study examined hearing loss prevalence and hearing aid usage rates among Korean elders by comparing the differences between those with and without hearing loss, and between those who used and did not use hearing aids. Methods: This study was based on data collected during the Korean National Health and Nutrition Examination Survey V (2010-2012). The study sample consisted of 5,447 Koreans aged ≥60 years who received a hearing assessment. Hearing loss was measured using a pure tone audiometry test and classified according to the World Health Organization's criteria. Hearing aid use was assessed by self-report. Multiple logistic regression analyses were performed to determine the associations between hearing loss, hearing aid use, and related variables. Results: Hearing loss was found in 16.8% of the elders and only 15.9% of them used a hearing aid. Male (95% CI: 1.27-2.15), tinnitus (95% CI: 1.58-2.32), dizziness (95% CI: 1.05-1.73), and occupational noise exposure (95% CI: 1.32-2.38) were the variables most strongly associated with hearing loss after multivariate adjustment. Tinnitus (95% CI: 1.34-4.13) and occupational noise exposure (95% CI: 1.01-5.02) were strongly associated with hearing aid use after multivariate adjustment. Conclusion: More than half of South Korean elders aged ≥60 and older have hearing loss but the rate of hearing aid use is very low. An aural public health program should address modifiable risk factors, such as tinnitus and noise exposure, and non-modifiable risk factors associated with hearing loss in the elderly